ANÁLISE DA INTERAÇÃO ENTRE OS USOS DO BIM E OS PRINCÍPIOS DO LEAN CONSTRUCTION EM UM ESTUDO DE CASO - Borges, Rodrigo Magalhães Siqueira; Mota, Paula Pontes; Maia, Lucas Menezes; Barros Neto, José de Paula (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
To start the project of a new building, it is first necessary to analyse its financial feasibility. Consideration should be given to design characteristics, resources availability and risks involved. To make construction planning activities more efficient, Lean Construction (LC) concept was developed, seeking to maximize product value and reduce losses. As for Building Information Modeling (BIM), it has made possible to design virtual models that simulate construction. But can BIM and LC interact together as facilitators of construction process, complementing each other, or should they be analysed independently? From this approach, through a case study method, this paper aims to identify BIM Uses by analysing practical examples, and verify if the benefits provided by BIM are related to the LC essence. The object of this study was a large real estate building located in Fortaleza, Brazil. As a result, it was verified that the BIM Uses is strongly related to some LC principles. Therefore, if well used, BIM can be characterized as a powerful planning tool, in a manner similar to LC, promoting anticipation in decision making and reducing waste.